Design of a 4-DOF MR haptic master for application to robot surgery: virtual environment work - Oh, Jong-Seok; Choi, Seung-Hyun; Choi, Seung-Bok (Smart materials and structures, 2014)
This paper presents the design and control performance of a novel type of 4-degrees-of-freedom (4-DOF) haptic master in cyberspace for a robot-assisted minimally invasive surgery (RMIS) application. By using a controllable magnetorheological (MR) fluid, the proposed haptic master can have a feedback function for a surgical robot. Due to the difficulty in utilizing real human organs in the experiment, the cyberspace that features the virtual object is constructed to evaluate the performance of the haptic master. In order to realize the cyberspace, a volumetric deformable object is represented by a shape-retaining chain-linked (S-chain) model, which is a fast volumetric model and is suitable for real-time applications. In the haptic architecture for an RMIS application, the desired torque and position induced from the virtual object of the cyberspace and the haptic master of real space are transferred to each other. In order to validate the superiority of the proposed master and volumetric model, a tracking control experiment is implemented with a nonhomogenous volumetric cubic object to demonstrate that the proposed model can be utilized in real-time haptic rendering architecture. A proportional-integral-derivative (PID) controller is then designed and empirically implemented to accomplish the desired torque trajectories. It has been verified from the experiment that tracking the control performance for torque trajectories from a virtual slave can be successfully achieved.